Cost-effectiveness of Ruxolitinib vs Best Available Therapy in the Treatment of Myelofibrosis in Spain - María Teresa Gómez-Casares; Juan Carlos Hernández-Boluda; Antonio Jiménez-Velasco; Joaquin Martínez-López; María Giovanna Ferrario; Irmina Gozalbo; Joana Gostkorzewicz; Rudi Subirá (Journal of Health Economics and Outcomes Research)
**Introduction:** Primary myelofibrosis (MF) is a rare hematologic disease belonging to the group of Philadelphia-negative chronic myeloproliferative neoplasms. Identification of the Janus Kinase (JAK) gene mutations inaugurated a new era in the targeted therapy of myeloproliferative diseases. Ruxolitinib is the first JAK1/JAK2 inhibitor specifically approved for the treatment of disease-related splenomegaly or symptoms in adult patients with primary myelofibrosis. The objective of this study was to assess the cost-effectiveness of ruxolitinib vs best available therapy (BAT) in MF patients in Spain.